Analisis Return on Equity (ROE), Current Ratio (CR), Net Profit Margins (NPM), dan Debt to Equity Ratio (DER) terhadap Earning Per Share (EPS): Analysis of Return on Equity (ROE), Current Ratio (CR), Net Profit Margins (NPM), and Debt to Equity Ratio (DER) to Earning Per Share (EPS) - Sriyono, Sriyono; Prapanca, Detak; Budi, Andi Setyo (Universitas Muhammadiyah Sidoarjo, 2018)
The purpose of this study is to influence of Return on Equity (ROE), Current Ratio (CR), Net Profit Margin (NPM) and Debt To Equity Ratio (DER) to Earning Per Share (EPS) are partially and simultaneously. The research methode is Quantitative with sample research methods are food and beverage manufacturing companies period 2012 to 2016 with a total of 12 companies. Data from the IDX Faculty of Economics and Business, University of Muhammadiyah Sidoarjo or from the official website of the IDX. Data collection is carried out by tracking financial statements, annual reports (annual reports) and continuous reports or social information of the companies selected as samples. The results showed that simultaneously (Test F) Return on Equity, Current Ratio, Net Profit Margin, and Debt to Equity Ratio, is significant effect on the company's Earning Per Share. Partially (t test) the variable Current Ratio (CR) has a negative effect on Earning Per Share. While the variable Return On Equity (ROE), Net Profit Margin (NPM), and Debt To Equity Ratio (DER) is not Significant effect on Earning Per Share.